Septic arthritis in neonates due to extended spectrum beta-lactamase producing Klebsiella pneumoniae - Outbreak analysis and long term follow-up - Indumathi, Vrithmani Aprameya; Ranganatha, C; Kempegowda, Punith (International Journal of Infection Control, 2012)
Between May and June 2002, we recorded and outbreak of Septic Arthritis in neonates due to Extended Spectrum Beta-Lactamase producing Klebsiella pneumoniae at our neonatal intensive care unit. The confirmed cases were then followed up to look for long term morbidities associated with the infection. We analyzed the microbiological and epidemiological features of the outbreak and the various measures implemented to ward off the same. We also studied the long term morbidities associated with nosocomial infection. All neonates admitted to the NICU during this period were screened and those with clinico-microbiological evidence of septic arthritis were included in the study. Microbiological screening of the environment, personnel, patients and their attendants were conducted and 85 different environmental sites were sampled. Six neonates were confirmed to have septic arthritis after an average NICU stay of 10.00±3.16 days. Culture of synovial fluid grew K. pneumoniae. All isolates had similar biochemical and antibiotic resistance pattern suggestive of clonality of infection. Plasmid analysis of these samples revealed a single plasmid (35.8MD) in all the isolates. Similar K. pneumoniae strain with the same plasmid was isolated from the water samples which was stored and used for hand washing. During the nine year follow up period, three neonates recovered completely, one developed dislocation of the joint and two were lost to follow up. Our study demonstrates the need for a comprehensive infection control measure and intensive monitoring of the NICUs for the ESBL producing K. pneumoniae.